Intensity and Prevalence of Ectoparasites in Common Carp (Cyprinus carpio) fry from Traditional Pond and “Longyam” at Sukamulya Villages, Singaparna, Tasikmalaya - Rustikawati, I.; Rostika, R.; Iriana, D.; Herlina, E. (Jurnal Akuakultur Indonesia, 2004)
The experiment was done to find out species, intensity and prevalence of common crap fry from traditional ponds and "longyam" at Sukamulya village, Singaparna, Tasikmalaya. This experiment was conducted at Sukamulya village and Aquatic Biology Laboratory of Fisheries Department, Faculty of Agriculture, Padjajaran University form October 1st 2002 to October 31th 2002. Samples of common carp fry were obtained from six traditional ponds and six "longyam". The survey method was used in this experiment of common carp fry at difference type of pond were based on the Wilcoxon rank sum test. Intensity and prevalence of ectoparasites of common carp fry at traditional ponds and longyam was based on the Kruskal-Wallis test. The result of this experiment showed that eight genera of ectoparasites were found, consisted of three Platyhelminthes: Dactylogyrus (47,01%), Gryrodactylus (3,84%), Transversotrema (0,01%), four Protozoa: Ichtyophthrius (9,59%), Epistylis (1,05%), Trichodina (1,68%) and one Arthopoda: Acarus (0,01%), The intensity of Dactylogyrus was 28,83. Gryrodactylus 4.98, Transversotrema 0,17, Ichthyophthirius 13,51, Epistylis 4,68, Trichodina 25,14 Trichodinella 6,55 and Acarus 0,17. The prevalence of Dactylogyrus is 90,00% Gyrodactylus 44,82%, Transversotrema 0,37%, Ichthyophthirius 42,17, Epistylis 13,17%, Trichodina 82,59%, Trichodinella 17,04 and Acarus 0,37%. Key words: Intensity, prevalence, ectoparasites, common carp fry, traditional pond, "longyam"